Pandemia, rezago y abandono escolar: sus factores asociados (Investigaciones) - Carro Olvera, Adriana (2022)
This article aims to know the associated factors regarding school lag and dropout during the health crisis in basic education in Tlaxcala, Mexico. This research was carried out with a quantitative descriptive methodology with analysis units associated with school dropouts in the COVID-19 pandemic context. The information was obtained through an online survey of 840 teachers from all levels and educational modalities. The results reflect a decrease in school enrollment and the difficulty to keep participation and communication with students, as well as an adverse socio-economic and socioemotional effect on most of the school population, along with the limitations in the arrangement and use of educational equipment and materials.